Implementation of Guided Discovery Learning to Improve Science Skills Process in Solar System Material - Saputro, Eko Wahyudi; Subekti, Hasan (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The aim of the research is to describe the applicability of using guided discovery learning on solar system material, improving science process skills using guided discovery learning models on solar system material, as well as students' responses after learning. The type of research used is one group pretest posttest. Data collection using the method of observation, tests, and questionnaires. The instruments used included learning implementation sheets, LKPD, pretest posttest, and response questionnaires. The results of the data show that the implementation of learning obtains an average score of 93% in the very good category. The increase in science process skills has increased by 0.47 in the moderate category. The student response questionnaire gave a response of 82% in the very good category